EKUILIBRASI PERKEMBANGAN KOGNITIF DALAM PRESTASI BELAJAR SISWA PROGRAM ILMU-ILMU KEAGAMAAN DI MADRASAH ALIYAH NEGERI 4 JOMBANG - Habibatul Mukaromah; Jasminto; Syamsuddin (EL-Islam, 2020)
Abstract: Education can not be separated from cognitive development that can grow and develop the potential in a child. In accordance with Jean Piaget's cognitive theory that in adolescence occurs at the fourth stage, namely formal operations. This study aims to determine the equilibration of cognitive development in adolescence that affects learning achievement. Through guidance, teachers can provide appropriate services to overcome problems in learning in accordance with the level of cognitive development. The methodology in this study uses a qualitative research approach and type of case study studies by collecting data from observations, interviews and documentation. In analyzing the data using Miles Huberman data analysis. The results show that in equilibration cognitive development in adolescence is a balance in the ability to think at the formal operational stage which is characterized by the ability to think abstractly and logically in solving a problem through the process of adaptation, assimilation and accommodation so that optimal performance appears. Keywords: Cognitive Development, Learning Achievement, Jean Piaget Abstrak: Pendidikan tidak lepas dari perkembangan kognitif yang dapat menumbuh kembangkan potensi pada diri seorang anak. Sesuai dengan teori kognitif Jean Piaget bahwa pada masa remaja terjadi pada tahap keempat yaitu operasional formal. Kajian ini bertujuan untuk mengetahui ekuilibrasi perkembangan kognitif pada masa remaja yang mempengaruhi prestasi belajarnya. Melalui bimbingan, guru dapat memberikan layanan yang tepat untuk mengatasi permasalahan dalam belajarnya sesuai dengan tingkat perkembangan kognitifnya. Metodologi pada kajian ini menggunakan pendekatan penelitian kualitatif dan jenis kajian studi kasus dengan mengumpulkan data dari hasil observasi, wawancara dan dokumentasi. Dalam analisis datanya menggunakan analisis data Miles Huberman. Hasil menunjukkan bahwa dalam ekuilibrasi perkembangan kognitif pada masa remaja adalah keseimbangan dalam kemampuan berpikir pada tahap operasional formal yang ditandai dengan kemampuan berpikir abstrak dan logis dalam memecahkan suatu permasalahan melalui proses adaptasi, asimilasi dan akomodasi sehingga nampak prestasi yang optimal. Kata Kunci: Perkembangan Kognitif, Prestasi Belajar, Jean Piaget